“MARGANEC TOPARSHASÍ ELEMENTLERI” TEMASÍN OQÍTÍWDA KEYSSTADI USÍLÍNAN PAYDALANÍW - Aymurzaeva, L.G.; Aytbaeva, X.B.; Kamalova, M.O. (SCIENCE and SOCIETY, 2024)
This article provides information on the procedure for conducting a case study in a chemistry lesson and conducting a mini-case in a chemistry lesson on the topic “Elements of the Manganese group.” Studying the topic “Elements of the Manganese group” using interactive educational technologies helps improve students’ knowledge, develop theoretical and practical skills, and increase the effectiveness of classes.